Research on the Identification of Precursor Information of Limestone Rockburst under Triaxial Unloading Conditions - Wenjun Ding; Zonghong Zhou; Jian Liu; Tingkai Hou; Jiaxin Wang; Jin Li; Xin Zhang (Geofluids)
Based on the energy evolution of limestone and acoustic emission evolution law, this paper takes the limestone unloading energy evolution law and acoustic emission cumulative ringing count, cumulative energy, RA value, acoustic emission information entropy, and acoustic emission damage as precursor discrimination indicators for the occurrence of rock explosion. Study of the impact of the unloading rate on the rock explosion precursors indicates that with increasing unloading rate there are more dramatic changes in the degree of each precursor discrimination indicators and rock ruptures within a short period of time before the completion of the indicators. The establishment of the precursor response coefficient reveals that the precursor response is the strongest when the rock rupture acoustic emission RA value time is the earliest. The remaining four precursor discrimination indicators of rock rupture with different loading paths show fluctuations in the identification capacity of the state. The research results can provide some reference for identifying rockburst precursor information.